2006
DOI: 10.1152/ajprenal.00287.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II on the CO2dependence of HCO3reabsorption by the rabbit S2 renal proximal tubule

Abstract: M tended to reduce stimulation by CO2, and at 10 Ϫ9 M, produced an even greater reduction. In conclusion, the mutual effects of 1) ANG II on the JHCO 3 response to basolateral CO2 and 2) basolateral CO2 on the JHCO 3 responses to ANG II suggest that the signal-transduction pathways for ANG II and basolateral CO2 intersect or merge.kidney; out-of-equilibrium solutions; acid-base; volume reabsorption ONE OF THE MAJOR tasks of the kidneys is to participate, along with the lungs, in the regulation of the acid-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…Our previous work shows that the stimulatory effect of low-dose ANG II (applied to either the apical or basolateral side) on HCO 3 Ϫ reabsorption is greatest at low levels of basolateral CO 2 and falls as CO 2 approaches 20%. These results are consistent with the idea that the signaltransduction pathways for ANG II and basolateral CO 2 intersect or perhaps even merge to produce similar end effects (88).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Our previous work shows that the stimulatory effect of low-dose ANG II (applied to either the apical or basolateral side) on HCO 3 Ϫ reabsorption is greatest at low levels of basolateral CO 2 and falls as CO 2 approaches 20%. These results are consistent with the idea that the signaltransduction pathways for ANG II and basolateral CO 2 intersect or perhaps even merge to produce similar end effects (88).…”
supporting
confidence: 88%
“…We (88) as well as others (43,80) have observed that adding a low dose of ANG II to the lumen increases J HCO 3 . On the other hand, adding higher doses of ANG II to the lumen either has no effect or reduces J HCO 3 (80,88). Presumably, the actual luminal ANG II concentration ([ANG II]) in these studies is the sum of secreted and added ANG II, Although it is possible that the very addition of exogenous ANG II modifies the secretion of endogenous ANG II.…”
Section: Endogenous Angiotensin Production By Pt Cellsmentioning
confidence: 88%
See 1 more Smart Citation
“…The values that we report for J HCO 3 (or JV) in the second collection period are normalized, mean values computed as described previously (60,61). Briefly, in each experiment, we divided the J HCO 3 (or JV) value obtained during the second collection period by the comparable value obtained during the first collection period; the result was a pair of second/first collection period ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol was virtually identical to the one that we used in previous studies (32)(33)(34)(35) except that, in the present study, we added lisinopril (a gift from Merck, Rahway, NJ), a specific ACE inhibitor, to the luminal or basolateral solution.…”
Section: Methodsmentioning
confidence: 99%